2017
DOI: 10.3177/jnsv.63.200
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Ingestion Suppresses Hyperglycemia in Streptozotocin-Induced Diabetic Mice

Abstract: Summary Coffee consumption reduces the risk of type 2 diabetes in humans, but the mechanism remains unclear. In this study, we investigated the effect of coffee on pancreatic b-cells in the induction of diabetes by streptozotocin (STZ) treatment in mice. We examined the effect of coffee, caffeine, or decaffeinated coffee ingestion on STZ-induced hyperglycemia. After STZ injection in Exp. 1 and 2, serum glucose concentration and water intake in coffee ingestion (Coffee group) tended to be lowered or was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Extensive epidemiological studies have shown that consumption of coffee is conducive for preventing diabetes, and studies have shown that caffeine, chlorogenic acid, and trigonelline in coffee have been shown to exert certain antidiabetic activities through different mechanisms. However, little research has been done on whether the trace components in coffee exert antidiabetic activity. α-Glucosidase plays a key role in the metabolism of carbohydrates in the human body and is considered to be an important target for the control of diabetes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Extensive epidemiological studies have shown that consumption of coffee is conducive for preventing diabetes, and studies have shown that caffeine, chlorogenic acid, and trigonelline in coffee have been shown to exert certain antidiabetic activities through different mechanisms. However, little research has been done on whether the trace components in coffee exert antidiabetic activity. α-Glucosidase plays a key role in the metabolism of carbohydrates in the human body and is considered to be an important target for the control of diabetes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Seperti yang disebutkan oleh (Anwari, 2021) kopi mempunyai kandungan asam klorogenat bisa melakukan penurunan kadar glukosa darah yakni dengan melakukan pencegahan timbulnya sel beta pankreas yang gagal dalam melakukan produksi insulin. Penelitian yang dilaksanakan (Misato et al, 2017) menyebutkan yakni asam klorogenat bekerja dengan cara melakukan penghambatan kegitan translokasa glukosa-6 fosfat. Terhalangnya tahapan-tahapan ini mengakibatkan glukosa yang terserap pada saluran gastrointestinal menjadi delay yang lalu akan memberikan rangsangan sekresi dari glucagon-like peptide 1 (GLP-1).…”
Section: Pembahasanunclassified